Response of Corriedale and Crioula Lanada sheep to artificial primary infection with Haemonchus contortus - Bricarello, P. A.; Gennari, S. M.; Oliveira-Sequeira, TCG; Vaz, CMSL; de Goncalves, I. G.; Echevarria, FAM (Kluwer Academic Publ, 2002)
Clinical, parasitological and biochemical parameters were evaluated in Corriedale and Crioula Lanada sheep after a single experimental infection with Haemonchus contortus. Ten 4-month-old worm-free lambs, of each breed, were infected with 200 L-3 H. contortus per kg live weight,and four uninfected animals of each breed were used as controls. Every week, the animals were weighed and blood and faecal samples were collected for measurement of packed cell volume (PCV), total serum protein (TSP) and albumin (ALB), and the number of eggs per gram of faeces (EPG), respectively. Twelve weeks after infection, the animals were slaughtered. The worm burden was determined and samples of the abomasal mucosa were processed for determination of the number of eosinophils, mast cells and globule leukocytes. No significant differences in PCV, TSP, ALB, parasite burden or the cell populations of the abomasal mucosa were observed between breeds, but Crioula lambs had a lower EPG count. The comparison of the infected groups with their respective controls revealed significant alterations in PCV, TSP and ALB in the Corriedale lambs and in PCV, TSP, ALB and the density of eosinophils and mast cells in the Crioula lambs.
Keywords: breed; burden; Corriedale; Crioula Lanada; Haemonchus contortus; helminthology; pathology; sheep